ITERA Botanical Garden Development Recommendation as a Feeding and Roaming Habitat for the Black-Winged Kite (Elanus caeruleus) - Hetharia, Bartholomew Jordan; Hutriani, Ina Winiastuti; Ali, Muhammad Saddam (The Ethnobiological Society of Indonesia, 2025)
Indonesia ranks fourth globally in bird species diversity. The Sumatera Institute of Technology (ITERA) Campus, with its diverse vegetation, supports at least 28 avian species, including the black-winged kite (E.caeruleus), a protected diurnal bird of prey. This species is protected in Indonesia and listed as Appendix II under CITES. One prominent area for these birds is the ITERA Botanical Garden, which has potential as a suitable habitat. This study aims to (1) analyze habitat suitability for the black-winged kite and (2) propose a landscape plan to support the species conservation in the ITERA Botanical Garden. Using mixed methods and a modified Gold landscape planning framework which includes inventory, landscape analysis, and synthesis, the research identifies the garden as a critical feeding and roaming area for the species. Results show that the ITERA Botanical Garden provides essential feeding and roaming areas for black-winged kites. The proposed concept,